Could chips and nuts be vector of food-borne outbreaks during happy hour?. (13th November 2019) - Gori, F; Cuccaro, C; Santamaria, M; Cardaci, R; Burgassi, S; Battaglia, M A; Messina, G
Abstract: Background: A Greater tendency to eat meals outside the home has led to an increase in the attendance of restaurants, cafes, and fast food. That is one of the reasons why the global interest in handling food has risen over the years. The aim of this study is to understand the level of microbial contamination in the food that is served along happy hour in cafe. Methods: This cross sectional pilot study was performed from April to May 2018 in the city of Siena, central Italy (<60000 citizens). Ten cafes were randomly selected. Samples of peanuts and potatoes were obtained in three different moments, at the beginning (T0), in the middle (T1), at the end (T2) of happy hours events. Collection of the samples was obtained using sterile kit and laboratory analysis was conducted in the University lab. The samples were located on selective medium and the growth of microbial pathogens were checked at 24 and 48 hours. The tested microorganisms were Enterococci, Staphylococci, Coliforms bacteria, Molds, and Yeasts. The statistical analyses were conducted using the Wilcoxon test using Stata 12. Results: A significant Yeasts contamination appeared only on chips at T0, while within T0 and T1 we found a significant increase of Enterococci, Staphylococci, and Yeasts (p < 0.05) both in peanuts and chips. Comparing T1 and T2 only Yeasts showed significant growth in potatoes (p = 0.04). Between T0 and T2 we also found the growth of Coliforms bacteria in peanuts (p = 0.03). Conclusions: We showed an increase in the microbial load associated with food handling, mostly of Enterococci. Long exposure time increased the likelihood of contamination and the possibility to exceed the dose for the occurrence of good outbreak. It is likely that offering small portions of handling food would reduce the manipulation by participants and the risk of food-borne outbreaks. Key messages: Define the most frequent microrganisms could be associated with backed food and evaluate which one of these can exceed the dose for the occurrence of disease in long time. Reflect on the likelihood that the risk of food-borne outbreak caused by manipulation of happy hour participants, may result in an increase in hospital admissions.